2023
DOI: 10.1002/adhm.202300395
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Methacryloyl Hydrogel, from Standardization, Performance, to Biomedical Application

Abstract: Gelatin methacryloyl (GelMA), a photocurable hydrogel, is widely used in 3D culture, particularly in 3D bioprinting, due to its high biocompatibility, tunable physicochemical properties, and excellent formability. However, as the properties and performances of GelMA vary under different synthetic conditions, there is a lack of standardization, leading to conflicting results. In this study, a uniform standard is established to understand and enhance GelMA applications. First, the basic concept of GelMA and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 132 publications
1
50
0
Order By: Relevance
“…GelMA contains abundant arginine-glycine-aspartic acid (RGD) sequences that favor cell attachment. 36 Intriguingly, TCP group exhibited more elongation and spreading form, while for hydrogel group, the cells displayed spheroid-like aggregation and clustering, and the mean diameter of stiff group was larger than that of soft group. The biocompatibility of GelMA hydrogel was determined with a calcein AM/PI cell viability/cytotoxicity assay kit (green: live cell; red: dead cell) (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…GelMA contains abundant arginine-glycine-aspartic acid (RGD) sequences that favor cell attachment. 36 Intriguingly, TCP group exhibited more elongation and spreading form, while for hydrogel group, the cells displayed spheroid-like aggregation and clustering, and the mean diameter of stiff group was larger than that of soft group. The biocompatibility of GelMA hydrogel was determined with a calcein AM/PI cell viability/cytotoxicity assay kit (green: live cell; red: dead cell) (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Presently, gelatin methacryloy can be used separately or in combination with other factors to form scaffolds relevant for bone engineering. [102,103] One of such scaffolds was developed by Zhang et al, [56,57] who designed a construct combining deferoxamine@poly(𝜖caprolactone) nanoparticles (DFO@PCL NPs), manganese carbonyl (MnCO) nanosheets, and a polylactide-hydroxyapatite (PLA-HA) with gelatin methacryloyl hydrogel. The idea behind the scaffold was to balance the mechanisms driving the immune system and bone metabolism.…”
Section: Figurementioning
confidence: 99%
“…Another paper from our group demonstrated that the transfection efficiency of PEGylated and plasmid-encapsulated chitosan nanoparticles could be promoted and that ANN could be an important tool for nanoparticle-mediated gene delivery systems . To date, researchers have investigated the parameters affecting hydrogel stiffness; ,, the machine-learning-driven prepolymer formulation for GelMA hydrogels required for different biomedical applications is yet to be found. Our study is unique and original for two reasons: (i) the stiffness and mechanical properties of previously published papers have no physiological relevance and so they do not have potential for tissue engineering applications and clinical use, and (ii) for the first time in the literature, we combined an ANN model with our experimental observations to standardize and effectively predict the critical parameters of GelMA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Protein-based hydrogels, including collagen, fibrin, elastin, and gelatin, have been widely employed in various biomedical applications . Gelatin methacryloyl (GelMA) is the most commonly studied hydrogel in tissue engineering applications such as 3D culture, , organ-on-a-chip, 3D bioprinting, ,, tissue engineering, , and drug/gene delivery. GelMA contains cell-binding (Arg-Gly-Asp (RGD)) and matrix-metalloproteinase (MMP)-sensitive degradation sites and may be customized to match many of the key characteristics of the natural extracellular matrix (ECM) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation